Pengaruh stimulasi psiko-sosial terhadap perkembangan sosio-emosional pada anak stunting di Aceh Tengah - Sarentya Fathadhika; Sri Redatin Retno Pudjiati (AcTion: Aceh Nutrition Journal, 2023)
Children who experience stunting are known to have problems in socio-emotional development. One of the factors that can help optimize children's socio-emotional development is the provision of psycho-social stimulation. This study aims to determine the effect of psychosocial stimulation on the socio-emotional development of stunted children in Central Aceh. This study uses a quantitative approach with a correlation cross-sectional research design. This research was conducted in February 2021. One hundred children aged 3 to 5 years with stunting conditions in Central Aceh were selected as participants in this study through convenience sampling. The measuring instruments used in this study are Ages & Stages Questionnaires: Social-Emotional, Second Edition (ASQ: SE-2) to measure children's socioemotional development and The Early Childhood Home Observation for Measurement of Environment (ECHOME). The analysis uses linear regression and multiple regression. The results showed no effect on providing psycho-social stimulation on socio-emotional development in stunted children in Central Aceh (p= 0,063). Furthermore, the results showed that language stimulation affected socio-emotional development (p= 0,003). In conclusion, overall psycho-social stimulation does not affect the socio-emotional development of stunted children in Central Aceh, and only language stimulation significantly affects socio-emotional development.